2016
DOI: 10.12816/0026149
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphism of Toxoplasma Gondii from Recently Infected Aborted Egyptian Women

Abstract: Toxoplasmosis caused by Toxoplasma gondii is one of the most prevalent parasitic diseases in human beings. Human toxoplasmosis can be associated with serious clinical manifestations, particularly in developing fetus. The aim of the current study was to identify the possible lineage type of Toxoplasma gondii, molecularly detected in placental samples of women whose pregnancies were spontaneously terminated in the first trimester. Preliminary detection of Toxoplasma genomic materials was done by a SYBR green qPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…1 shows the amplification plot of the real-time PCR reaction for product positive samples for the T. gondii parasite diagnosis by B1 gene, where the (yaxis) represents the dye measurement unit while the (xaxis) represents the thermal cycles of the reaction. This result higher than what recorded by Hernández-Cortazar et al (2016) a ratio (3.84%) by quantitative PCR and (6.92%) when using nested PCR at they examined 161 blood samples for aborted women in Mexico, while lower than Darweesh et al (2018) in Baqubah city/where they recorded (15%) infection rate by used real-time PCR, and with study Badr et al (2016) in Egypt when they used traditional Polymerase chain reaction to identify for T. gondii in aborted women and they recorded (12.5%), as well as with Al-nasrawi et al (2014) when they detected of the parasite in blood samples from aborts woman reviews for Al-Mothana hospital laboratory and record (16%) by using real-time PCR based TaqMan prob. Molecular diagnosis of toxoplasmosis is the most accurate and sensitive because the ability of this methods to diagnose the modern infection of the parasite before the body begins to form antibodies, while the serological examination depends on the formation of antibodies after several weeks from infection of the host parasite (Al-Mosawi et al 2015; Al- x 2 = 51.39 df = 1 P \ 0.05 *The results of the statistical analysis showed a significant difference between the percentage of IgG and IgM under the probability level P \ 0.05 abodi et al 2015), the difference in the results of the B technique between the current study and the other studies is due to differences in methods of extraction of DNA and its methods of work and to the amount of parasite in the sample, in addition to this type of sample under study and population density and surrounding environmental conditions (Al-abodi et al 2015).…”
Section: Resultscontrasting
confidence: 53%
“…1 shows the amplification plot of the real-time PCR reaction for product positive samples for the T. gondii parasite diagnosis by B1 gene, where the (yaxis) represents the dye measurement unit while the (xaxis) represents the thermal cycles of the reaction. This result higher than what recorded by Hernández-Cortazar et al (2016) a ratio (3.84%) by quantitative PCR and (6.92%) when using nested PCR at they examined 161 blood samples for aborted women in Mexico, while lower than Darweesh et al (2018) in Baqubah city/where they recorded (15%) infection rate by used real-time PCR, and with study Badr et al (2016) in Egypt when they used traditional Polymerase chain reaction to identify for T. gondii in aborted women and they recorded (12.5%), as well as with Al-nasrawi et al (2014) when they detected of the parasite in blood samples from aborts woman reviews for Al-Mothana hospital laboratory and record (16%) by using real-time PCR based TaqMan prob. Molecular diagnosis of toxoplasmosis is the most accurate and sensitive because the ability of this methods to diagnose the modern infection of the parasite before the body begins to form antibodies, while the serological examination depends on the formation of antibodies after several weeks from infection of the host parasite (Al-Mosawi et al 2015; Al- x 2 = 51.39 df = 1 P \ 0.05 *The results of the statistical analysis showed a significant difference between the percentage of IgG and IgM under the probability level P \ 0.05 abodi et al 2015), the difference in the results of the B technique between the current study and the other studies is due to differences in methods of extraction of DNA and its methods of work and to the amount of parasite in the sample, in addition to this type of sample under study and population density and surrounding environmental conditions (Al-abodi et al 2015).…”
Section: Resultscontrasting
confidence: 53%
“…Toxoplasma gondii is compose, parasite protozoan intracellular that worldwide spreading. Humans Infection is commonly wanting incidental, but it ability apparent itself in a several form in cases of congenital toxoplasmosis and in immune compromised individuals ( 10).In this study results of statical analysis the chi-square χ 2 of patients have shown (13.82) and control (15.75) are significant in nPCR mean to high infection in Iraqi women . Some studied presented that a single T. gondii parasite could be detected by PCR (8) agreement with this study.…”
Section: Resultsmentioning
confidence: 63%
“…In Europe and the U.S., archetypical clonal lineages (Types I, II, and III) predominate, while the genotypical profile of T. gondii varies greatly in Brazil, with an increasing number of atypical strains. Atypical strains cause severe toxoplasmosis in immunocompetent patients and congenital toxoplasmosis newborns (20) .…”
Section: Discussionmentioning
confidence: 99%